2013
DOI: 10.1126/science.1228519
|View full text |Cite
|
Sign up to set email alerts
|

Current-Driven Spin Dynamics of Artificially Constructed Quantum Magnets

Abstract: The future of nanoscale spin-based technologies hinges on a fundamental understanding and dynamic control of atomic-scale magnets. The role of the substrate conduction electrons on the dynamics of supported atomic magnets is still a question of interest lacking experimental insight. We characterized the temperature-dependent dynamical response of artificially constructed magnets, composed of a few exchange-coupled atomic spins adsorbed on a metallic substrate, to spin-polarized currents driven and read out by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
211
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 202 publications
(227 citation statements)
references
References 48 publications
8
211
1
Order By: Relevance
“…Dimers of transition metals, as the small-size end point of SMMs, have been theoretically proposed to be promising candidates for novel information storage devices 6 . An alternative approach for the design of magnetic materials based on a few or even single atoms as magnetic units is ad-atoms on metallic surfaces 7,8 . The key property among these actually very different examples, and of any nanoscale magnetic system, is a large magnetic anisotropy energy.…”
mentioning
confidence: 99%
“…Dimers of transition metals, as the small-size end point of SMMs, have been theoretically proposed to be promising candidates for novel information storage devices 6 . An alternative approach for the design of magnetic materials based on a few or even single atoms as magnetic units is ad-atoms on metallic surfaces 7,8 . The key property among these actually very different examples, and of any nanoscale magnetic system, is a large magnetic anisotropy energy.…”
mentioning
confidence: 99%
“…Long wave-length excitations of complex magnets such as yttrium iron garnet (YIG) can be treated by such a model by coarse graining, i.e., letting each spin represents the magnetization of a unit cell. Artificially fabricated exchangecoupled atomic spins on a substrate [17] is another physical realization of this model. The magnetization dynamics can be described by the so-called Landau-Lifshitz-Miyazaki-Seki (LLMS) equations [11]:…”
Section: Modelmentioning
confidence: 99%
“…The memory kernel with relaxation time τ c does not affect the repartition. Although we consider an exponential memory kernel here, we envision that the obtained energy repartition principle (17) should be robust to the specific form of the kernels. The generalization to two spins in the unit cell leads to acoustic and optical magnon branches and can be used to study ferrimagnets and antiferromagnets [27].…”
Section: A Linear Spin-wave Theorymentioning
confidence: 99%
“…Particularly recent advances in scanning tunneling microscopy lead to enormous progress in the probing and manipulation of these systems including writing, reading, and processing of information from atomic scale bits via e.g. spintransfer torques [14,15] and spin-polarized spectroscopy techniques [16,17].In all of these cases, the coupling between adatom and substrate is central to determine the magnetic properties of the system. Thus, changes in the quantum state of the substrate can directly affect the adatom magnetism, as studies of superconducting substrates demonstrated [18,19].…”
mentioning
confidence: 99%
“…Particularly recent advances in scanning tunneling microscopy lead to enormous progress in the probing and manipulation of these systems including writing, reading, and processing of information from atomic scale bits via e.g. spintransfer torques [14,15] and spin-polarized spectroscopy techniques [16,17].…”
mentioning
confidence: 99%